Experimental Investigation of Spirulina Microalgae Biodiesel with Metal Nanoadditive on Single-Cylinder Diesel Engine. (7th January 2022) - Arunprasad, J.; Sener, Arif Senol; Thirugnanasambantham, R.; Elango, T.; Bothichandar, T.
Abstract : Nanoparticles are an emerging concept for increasing fuel properties. The purpose of this research work is to determine the effect of magnesium oxide nanoparticles on the performance and emission characteristics of diesel engines that run on a spirulina microalgae biodiesel blend (B20) as a fuel. The ultrasonication was used to disperse MgO nanoparticles in B20 fuel at various concentrations (25, 50, 75, and 100 ppm). The significant findings indicated that B20+100 blends reduced specific fuel consumption by 20.1% and had a 5.09% higher brake thermal efficiency than B20. B20+100 blends reduced CO, hydrocarbon, and smoke emissions by a maximum of 32.02%, 30.03%, and 26.07%, respectively, compared to B20.